Language Distribution in Sakha Family Communication: Traditions and Innovations - N. I. Ivanova (Научный диалог, 2023)
The article explores the issue of language reproduction in family communication among the Yakut people in the context of transformational tendencies in the development of urban families during the industrialization era. Using a multidisciplinary approach and sociolinguistic surveys conducted in 2007, 2014, and 2021, the study aims to identify dynamic changes in the functioning of the native (ethnic) language in family communication among rural and urban Yakut people. The results show that the ethnic function of the Yakut language is relevant only for half of urban Yakut families (52.1%) and 89.2% of rural Yakut families. In the context of general social transformation of the family institution, the main findings indicate a reduction in the volume of communication with children in everyday communication, a decrease in intergenerational family communication space on the ethnic language (grandmothers communicating with grandchildren), and a slight increase in parental communication with children. The social function of the ethnic language in rural family communication remains stable due to relative mono-ethnicity and geographical remoteness, but the introduction of digitization into everyday language use leads to cases of younger children switching to another language.